2007
DOI: 10.1128/aem.02439-06
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by and Antifungal Susceptibility of Candida Isolates from Urine

Abstract: Biofilm formation (BF) in the setting of candiduria has not been well studied. We determined BF and MIC to antifungals in Candida spp. isolates grown from urine samples of patients and performed a retrospective chart review to examine the correlation with risk factors. A total of 67 Candida spp. isolates were grown from urine samples from 55 patients. The species distribution was C. albicans (54%), C. glabrata (36%), and C. tropicalis (10%). BF varied greatly among individual Candida isolates but was stable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
94
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 44 publications
21
94
3
2
Order By: Relevance
“…However, it should be emphasized that only a few isolates were used and other isolates belonging to the same species may be able to form stronger biofilms. Furthermore, the authors verified that, as previously recognized (Jain et al, 2007;Uppuluri et al, 2009), an increase of sugars (which could be representative of diabetic patients) is a requirement for increased biofilm formation (data not shown). Furthermore, fungal infections are also more common in patients with diabetes, particularly those involving Candida species, occasionally causing dramatic clinical repercussions with obstruction of the urinary catheter (Patterson & Andriole, 1995).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…However, it should be emphasized that only a few isolates were used and other isolates belonging to the same species may be able to form stronger biofilms. Furthermore, the authors verified that, as previously recognized (Jain et al, 2007;Uppuluri et al, 2009), an increase of sugars (which could be representative of diabetic patients) is a requirement for increased biofilm formation (data not shown). Furthermore, fungal infections are also more common in patients with diabetes, particularly those involving Candida species, occasionally causing dramatic clinical repercussions with obstruction of the urinary catheter (Patterson & Andriole, 1995).…”
Section: Discussionsupporting
confidence: 72%
“…It is known that mature Candida biofilms are organized into structured communities embedded within a matrix of extracellular material that is produced by the biofilm cells (Al-Fattani & Douglas, 2006;Silva et al, 2009). Formation of mature biofilms and consequent production of matrix is strongly dependent on environmental conditions, such as medium composition, pH, oxygen, species and strains (Jain et al, 2007;Ramage et al, 2006). In fact, these particular isolates are not capable of forming dense 3D biofilms and producing enough matrix (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to this, we found that isolates derived from oral niches with GPD showed a significantly higher biofilm biomass compared to strains isolated in healthy oral conditions. This result was confirmed in two different culture media, RPMI 1640 and YPD, and agrees with reports by Hasan F. et al (2009) [54] and Jain N. et al (2007) [55], who also suggested that the origin and selection of isolates may be an influential factor in this Candida species biofilm formation. Furthermore, conversion of Candida species from commensalism to parasitism and their overgrowth are usually associated with changes in the intraoral environment such as unhygienic prostheses and xerostomia, or systemic factors such as type 2 diabetes (DM2) and immunodeficiencies.…”
Section: Discussionsupporting
confidence: 80%